PENGARUH KEPEMIMPINAN, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI PT JAYA LAND - Laily Rahmawati; Salman Paludi (LPPM Universitas Asa Indonesia, 2020)
This study aims to examine the effect of leadership, motivation, and compensation on employee performance at PT Jaya Land. Respondents were drawn from 80 employees of PT Jaya Land. The sampling technique uses saturated sampling technique. The data analysis technique used multiple linear regression analysis. The results of the analysis can be concluded that leadership, motivation and compensation have a positive and significant effect both simultaneously and partially on employee performance. For this reason, the Division Head at PT Jaya Land must maintain and enhance good role models, motivate employees and provide ideas and solutions for each problem and provide positive recognition to employees for their work, pay attention to employees and give awards so that employee performance remains good.